1997
DOI: 10.1007/s11746-997-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of phenolic compounds in virgin olive oil during storage

Abstract: Phenolic compounds are of fundamental importance to the shelf life of virgin olive oils because of their antioxidative properties. In this paper, the evolution of simple and complex olive oil phenols during 18 mon of storage is studied by high-performance liquid chromatography (HPLC) analysis. The olive oils under examination were from various olive cultivars, harvested in two sectors in the same region at different stages of ripeness. The findings indicate that it is not the variety but rather the ripeness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
2
8

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 7 publications
10
103
2
8
Order By: Relevance
“…The AC and TPC in the enriched oils after 2 and 4 wk of storage decreased about 22 and 27%, respectively, in comparison to the control refined rapeseed oil ( Table 4). The similar reduction of the TPC and AC of virgin olive oils (12.1-41.1 mg/100 g fresh olive oil; 0.6-14.6 mg/100 g olive after 18 months) and extra virgin olive oils treated with lycopene (TPC ¼ 70.0 mg/100 g and TEAC ¼ 0.70 mM at time ¼ 0 min; TPC ¼ 40.0-50.0 mg/100 g and TEAC ¼ 0.41-0.52 mM after 9 months) during storage was observed by Cinquanta et al [37] and Montesano et al [38].…”
Section: Ac and Tpc In The Refined And Enriched Rapeseed Oilsmentioning
confidence: 70%
“…The AC and TPC in the enriched oils after 2 and 4 wk of storage decreased about 22 and 27%, respectively, in comparison to the control refined rapeseed oil ( Table 4). The similar reduction of the TPC and AC of virgin olive oils (12.1-41.1 mg/100 g fresh olive oil; 0.6-14.6 mg/100 g olive after 18 months) and extra virgin olive oils treated with lycopene (TPC ¼ 70.0 mg/100 g and TEAC ¼ 0.70 mM at time ¼ 0 min; TPC ¼ 40.0-50.0 mg/100 g and TEAC ¼ 0.41-0.52 mM after 9 months) during storage was observed by Cinquanta et al [37] and Montesano et al [38].…”
Section: Ac and Tpc In The Refined And Enriched Rapeseed Oilsmentioning
confidence: 70%
“…This molecule is widely known for its high antioxidant ability and consequently correlated both to the antioxidant capacity of the MPC fraction and to the oil ageing resistance according to other authors. 28,29 To optimize the experimental conditions for quantitative purposes, the following steps were developed: (a) verification of the chemical stability of pure OH-Tyr in the applied experimental conditions; (b) control of the complete hydrolysis of the ester linkage of pure oleuropein and evaluation of the OH-Tyr content; (c) spiking MPC fractions with oleuropein to quantify the percentage recovery of OHTyr after acid hydrolysis.…”
Section: Results and Discussion Acid Hydrolysismentioning
confidence: 99%
“…Salvador et al (2001) reported that total phenolic content measured by the Folin-Ciocalteau method ranged from 19 to 380mg/kg, and from 124 to 516mg/kg according to Nissiotis and Tasioula-Margari (2002). The amount of phenols in crude seed oils is an important factor when evaluating the quality of the oit because these compounds have been correlated with col our, the shelf-life of oit and, in particular, its resistance to oxidation (Cinquanta et al, 1997). Pinus halepensis seed oil could be considered as a potential source of natural phenolic compounds.…”
Section: Sorne Quality Pararnetersmentioning
confidence: 99%